ACTIVITIES OF DAILY LIVING PADA PASIEN STROKE ISKEMIK - Pramana, Yoga; Hanafi, Hanafi; Maulana, M Ali; Seprian, Dwin (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Background: Ischemic stroke is a global health problem that causes significant mortality and disability worldwide, with a prevalence of approximately 6.2 million deaths annually. Ischemic stroke is the most common type of stroke in Indonesia, accounting for 87%. Objective: This study was conducted to determine the relationship between body mass index (BMI) and the level of dependency in ischemic stroke patients. Method: This is a descriptive analytical study with a cross-sectional approach. The cross-sectional sample used in this study consisted of 20 respondents, including ischemic stroke patients at Tanjungpura University Hospital, Pontianak. The sampling technique used was purposive sampling. Results: The Spearman Rank test showed significant results (2-tailed) with a p-value of 0.576, indicating no relationship between body mass index and Activities of Daily Living in ischemic stroke patients. Conclusion: There is no relationship between body mass index and Activities of Daily Living in ischemic stroke patients.